MANAGEMENT EDUCATION, TECHNOLOGY, AND PESANTREN FINANCIAL REPORTING QUALITY: ACCOUNTABILITY MEDIATION - Budi Gautama Siregar; Ali Hardana; Zaki Zaini (Finansha: Journal of Sharia Financial Management, 2026)
The quality of financial reporting is a critical issue for Indonesian pesantren as faith-based nonprofit institutions entrusted with managing public resources. Despite their rapid growth and increasing accountability demands, many pesantren continue to face challenges related to managerial competence, technological capability, and transparent financial governance. This study examines the effects of management education and technology on the quality of pesantren financial statements, with transparency as a mediating variable. Data were collected from 300 financial managers and administrators of pesantren in Indonesia using purposive sampling, targeting respondents directly involved in financial management and reporting. The proposed model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) because it is appropriate for mediation analysis, prediction-oriented research, and complex latent-variable models. The findings indicate that technology has a significant direct effect on financial reporting quality, whereas management education influences reporting quality indirectly through transparency. Transparency serves as a significant mediator, strengthening the relationship between managerial capacity and reporting quality. These results extend governance theory in faith-based nonprofit organizations by highlighting transparency as a strategic governance mechanism and enrich the religious accounting literature by demonstrating how managerial competence and digital transformation jointly enhance financial accountability in pesantren.